Recent Trends in Private Participation in Infrastructure - Roger, Neil (World Bank, Washington, DC, 2012)
Private activity in infrastructure - as measured by investment flows to projects with private participation - grew dramatically in developing countries between 1990 and 1997, from about US$16 billion to US$120 billion. It then declined by about a fifth to US$95 billion in 1998, a result of the Asian financial crisis that began in mid-1997. Private activity in 1998, sustained by a US$19 billion telecommunications privatization in Brazil, remained above the 1996 level. Investment over the past eight years totaled nearly US$500 billion. Private investment now averages about 40 percent of the total for infrastructure in developing countries. More goes to telecommunications and energy than other sectors, and more to East Asia and Latin America than other regions. But almost all developing countries have some private activity in infrastructure.